2019
DOI: 10.1093/ajh/hpz057
|View full text |Cite
|
Sign up to set email alerts
|

Greater Adherence to Life’s Simple 7 Is Associated With Less Arterial Stiffness: the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background Greater arterial stiffness is associated independently with increased cardiovascular disease risk. The American Heart Association (AHA) has recommended following “Life’s Simple 7 (LS7)” to optimize cardiovascular health; we tested whether better LS7 in middle age is associated with less arterial stiffness in later life. Methods We studied 4,232 black and white participants aged 45–64 years at the baseline (1987–89)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…Findings include strong inverse, stepwise associations in the United States of the number of CVH components at ideal levels with all-cause mortality, CVD mortality, IHD mortality, CVD, and HF; with subclinical measures of atherosclerosis such as carotid IMT, arterial stiffness, and CAC prevalence and progression; with physical functional impairment and frailty; with cognitive decline and depression; and with longevity. 3–8 Similar relationships have also been seen in non-US populations. 3,4,9–22…”
Section: Relevance Of Ideal Cvhsupporting
confidence: 68%
See 1 more Smart Citation
“…Findings include strong inverse, stepwise associations in the United States of the number of CVH components at ideal levels with all-cause mortality, CVD mortality, IHD mortality, CVD, and HF; with subclinical measures of atherosclerosis such as carotid IMT, arterial stiffness, and CAC prevalence and progression; with physical functional impairment and frailty; with cognitive decline and depression; and with longevity. 3–8 Similar relationships have also been seen in non-US populations. 3,4,9–22…”
Section: Relevance Of Ideal Cvhsupporting
confidence: 68%
“…Better CVH as defined by the AHA is associated with lower incidence of HF, 3,5–7,22 less subclinical vascular disease, 8,15,17,33,34 better global cognitive performance and cognitive function, 16,35,36 lower hazard of subsequent dementia, 37,38 lower prevalence 39 and incidence 40 of depressive symptoms, lower loss of physical functional status, 41 longer leukocyte telomere length, 42 less ESRD, 43 less pneumonia, less chronic obstructive pulmonary disease, 44 less VTE/PE, 45 lower prevalence of aortic sclerosis and stenosis, 46 lower risk of calcific aortic valve stenosis, 47 better prognosis after MI, 48 lower risk of AF, 49 and lower odds of having elevated resting heart rate. 50 Using the CVH scoring approach, the FHS demonstrated significantly lower odds of prevalent hepatic steatosis associated with more favorable CVH scores, and the decrease of liver fat associated with more favorable CVH scores was greater among people with a higher GRS for NAFLD.…”
Section: Relevance Of Ideal Cvhmentioning
confidence: 99%
“…Findings include strong inverse, stepwise associations in the United States of the number of CVH components at ideal levels with all-cause mortality, CVD mortality, IHD mortality, CVD, and HF; with subclinical measures of atherosclerosis such as carotid IMT, arterial stiffness, and CAC prevalence and progression; with physical functional impairment and frailty; with cognitive decline and depression; and with longevity. 4–9 Similar relationships have also been seen in non-US populations. 4,10–24…”
Section: Cardiovascular Healthsupporting
confidence: 68%
“…Better CVH as defined by the AHA is associated with a lower incidence of HF, 4,6–8,22 less subclinical vascular disease, 9,15,17,41,42 better global cognitive performance and cognitive function, 16,43 lower hazard of subsequent dementia, 44–46 fewer depressive symptoms, 47–49 longer leukocyte telomere length, 50 less ESRD, 51 less pneumonia, 52 less chronic obstructive pulmonary disease, 53 lower prevalence of aortic sclerosis and stenosis, 54 lower risk of calcific aortic valve stenosis, 55 better prognosis after MI, 56 lower risk of AF, 57,58 and lower odds of having elevated resting heart rate. 59 Using the CVH scoring approach, the FHS demonstrated significantly lower odds of prevalent hepatic steatosis associated with more favorable CVH scores, and the decrease of liver fat associated with more favorable CVH scores was greater among people with a higher GRS for NAFLD.…”
Section: Cardiovascular Healthmentioning
confidence: 99%
“…In contrast, a good CVH can mitigate the longitudinal progression of both subclinical atherosclerosis and arteriosclerosis. 15,16,[40][41][42][43] A recent autopsy study of elderly Japanese 44 reported partial correlations of aortic PWV and coronary atherosclerotic burden of about 0.19, which is remarkably similar to the pair-wise partial correlation in our investigation. To our knowledge, no prior study has evaluated the prognostic significance of the conjoint presence of CAC, higher CFPWV, and poor CVH.…”
Section: In the Context Of The Published Literaturesupporting
confidence: 89%